Peran Guru dalam Meningkatkan Karakter Disiplin Peserta Didik di SD Darul Hikam - Mubarok, Husni; Agustina, Erika; Mahya, Mazieda Salsabiela Bihar; Atho’illah, Abdul Halim; Rachma, Nisrina Aulia; Zuliana, Nila (TSAQOFAH, 2022)
Teachers are the most important part in the world of education. These components are needed in the process of formal and non-formal education. The role of the teacher in improving the character of students must be optimized, especially in terms of the character of discipline, so that in the future it can make students able to complete their school assignments well. The purpose of this research is to describe the teacher's role in improving the disciplined character of students in the Darul Hikam Elementary School in Bandung. This research method uses a descriptive qualitative approach, the informants are taken through snowball sampling technique. The data collection uses observation, interviews and documentation techniques. Data analysis techniques researchers use data reduction, data presentation, drawing conclusions or verification. In this study it can be concluded that the role of teachers in SD Darul Hikam Bandung in improving the character of discipline, namely: Teachers as educators, teachers as initiators and teachers as correctors.